2006
DOI: 10.1080/03602550600887285
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Submicron TiO2 Particles on the Mechanical Properties and Fracture Characteristics of Cured Epoxy Resin

Abstract: Submicron titanium dioxide (TiO 2 ) was used in different weight fractions as a toughening agent for amine-cured epoxy resin. After the use of X-ray photoelectron spectroscopy (XPS), which confirmed that the TiO 2 particles were evenly distributed in the cross-linked epoxy resin matrix, the composites were characterized by tensile and impact testing, followed by scanning electron microscopy of the fracture surfaces. The results indicated that the submicron TiO 2 toughening particles markedly improved the mecha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
55
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(59 citation statements)
references
References 16 publications
3
55
0
1
Order By: Relevance
“…실리카(SiO2) [1], 알루미나(Al2O3) [2], 마이카 [3], 질화알루미륨 (aluminumnitride : ALN) [4] 그리고 titanium dioxide(TiO2) [5] 와 같은 여러종류의 무기물필러들이 절연용 고분자 복합체 로서 사용 되고 있다. 특히, 실리카나 마이카는 고전압 중 전기기에 광범위하게 사용되고있다.…”
Section: 서 론unclassified
“…실리카(SiO2) [1], 알루미나(Al2O3) [2], 마이카 [3], 질화알루미륨 (aluminumnitride : ALN) [4] 그리고 titanium dioxide(TiO2) [5] 와 같은 여러종류의 무기물필러들이 절연용 고분자 복합체 로서 사용 되고 있다. 특히, 실리카나 마이카는 고전압 중 전기기에 광범위하게 사용되고있다.…”
Section: 서 론unclassified
“…Very few studies have been reported on the epoxy/TiO 2 nanocomposites, most of them are focused on the final mechanical properties [37,38]. However, the effect of TiO 2 on cure, rheology, and volume shrinkage of epoxy systems has never been investigated.…”
Section: Journal Of Polymersmentioning
confidence: 99%
“…We can think that there is an optimum filler amount that can be dispersed in the ESBO matrix. If this ratio is exceeded, then the filler is not able to establish maximum interaction with ESBO-NMA crosslinked structure thus leading to stress concentration which is responsible for a decrease in mechanical performance [39] . In conclusion, adding an amount of more than 15 wt.…”
Section: Figurementioning
confidence: 99%